Reconceptualising manual therapy skills in contemporary practice - Rabey, M.; Hall, Toby; Hebron, C.; Palsson, T.; Christensen, S.; Moloney, N. (2017)
© 2017 Elsevier Ltd. With conflicting evidence regarding the effectiveness of manual therapy calls have arisen within some quarters of the physiotherapy profession challenging the continued use of manual skills for assessment and treatment. A reconceptualisation of the importance of manual examination findings is put forward, based upon a contemporary understanding of pain science, rathe r than considering these skills only in terms of how they should â€œguideâ€? manual therapy interventions. The place for manual examination findings within complex, multidimensional presentations is considered using vignettes describing the presentations of five people with low back pain. As part of multidimensional, individualised management, the balance of evidence relating to the effectiveness, mechanisms of action and rationale for manual skills is discussed. It is concluded that if manual examination and therapeutic skills are used in a manner consistent with a contemporary understanding of pain science, multidimensional patient profiles and a person-centred approach, their selective and judicious use still has an important role.